Analysis of the Localization-based Model of the Pedestrian Zone Plans (Pedestrian-oriented streets) - Davood Habibi, Gholamreza Latifi, Mahmoud Rezaei, Reza Ahmadian, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Due to the increase in using the transportation and reduction in the environmental quality, especially in the central fabric of the cities, the efforts to improve the living conditions of people and returning the urban spaces to them are of significant importance. The pedestrian zone construction, as one of the policies towards the pedestrian orientation of the cities, has been significantly considered by many cities of the world since a half-century ago. However, the implementation of the pedestrian zones in different cities was associated with various results so that some of the pedestrian zones failed due to the lack of compatibility (localization) and were opened to the vehicles again. Therefore, the current study attempted to identify the valid indicators to study three pedestrian zones, including Chahar Bagh in Isfahan, Tarbiat in Tabriz, and 17 Shahrivar in Tehran. The research method was analytical-descriptive and based on the documentary and field studies. Also, Analytic Hierarchy Process Model was used for the comparative comparison of the samples to preserve all the relationships in the evaluation. The paired comparison of the nodes and clusters was conducted based on the opinions of the expert group (Delphi Method). The results showed that the quality of the Chahar Bagh pedestrian zone is higher than the others and has more compatibility with the conditions of the Iranian cities, and can be used as a successful model in the pedestrian zone construction in Iran.